Early addition of enzyme-treated soybean in the diet improves amino acid absorption and protein digestibility by promoting digestive enzyme activity in broilers - C.L. Ma; Z.C. Yin; X.Y. Zhang; C.X. Zhang; W.Y. Zhang; Y.X. Li; X.J. Yang (Animal)
Early nutritional regulation has become a research hotspot. The present study was undertaken to assess dietary early addition enzyme-treated soybean meal (ESBM) on nutrient digestibility, amino acid absorption, and intestinal development of broilers. Four hundred and fifty 1-day-old broilers were divided into three groups with 10 replicates of 15 broilers and fed with a basic diet, 2.5 or 5% ESBM during 1–10 days. Then, all groups were fed the same basic diets until 42 d. The obtained results indicated that supplementation of ESBM in early stage resulted in heavier BW and a better feed conversion ratio during the experimental periods compared with the control group. Supplementing the broiler’s diet with 5% ESBM led to enhance digestibility of DM, CP and decrease abdominal fat yield (P < 0.05). Meanwhile, 5% ESBM in the early diet increased villus height (P < 0.05, d 21) and reduced the crypt depth in jejunum and ileum (P < 0.05, d 42). Dietary 5% ESBM supplementation improved enzyme activity and upregulated nutrient transporters expression in jejunum, increased plasma amino acid (AA) concentrations (P < 0.05, d 10). In conclusion, our data demonstrated that supplementation ESBM promote intestinal development, upregulate AAs and peptide transporters gene expression for physiological absorption of AAs, and improve protein digestibility caused by intestinal enzyme activity, thereby improving growth performance.